2014
DOI: 10.3767/003158514x680207
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic circumscription of Arthrographis (Eremomycetaceae, Dothideomycetes)

Abstract: Numerous members of Ascomycota and Basidiomycota produce only poorly differentiated arthroconidial asexual morphs in culture. These arthroconidial fungi are grouped in genera where the asexual-sexual connections and their taxonomic circumscription are poorly known. In the present study we explored the phylogenetic relationships of two of these ascomycetous genera, Arthrographis and Arthropsis. Analysis of D1/D2 sequences of all species of both genera revealed that both are polyphyletic, with species being acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
(52 reference statements)
0
20
0
1
Order By: Relevance
“… Valmaseda et al (1986) erected the new monotypic genus Pithoascina for the arthroconidia-forming species P. langeronii. Based on these features, P. langeronii was later transferred to the genus Eremomyces ( Eremomycetaceae , Dothideomycetes ) by Malloch & Sigler (1988) and more recently to Arthrographis , being renamed as Arthrographis arxii ( Giraldo et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“… Valmaseda et al (1986) erected the new monotypic genus Pithoascina for the arthroconidia-forming species P. langeronii. Based on these features, P. langeronii was later transferred to the genus Eremomyces ( Eremomycetaceae , Dothideomycetes ) by Malloch & Sigler (1988) and more recently to Arthrographis , being renamed as Arthrographis arxii ( Giraldo et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notes — Pseudoarthrographis is morphologically similar to the genus Arthrographis , which also resides in the Dothideomycetes ( Eremomycetaceae ). Species of Arthrographis have been isolated from the air, compost, marine sediments, soil, wood and also from opportunistic human infections ( Giraldo et al 2014 ). Another genus to consider in this description is Arthropsis , which accommodates species with dark arthroconidia, joined by adjacent connectives and developing from undifferentiated conidiogenous hyphae ( Sigler et al 1982 ).…”
mentioning
confidence: 99%
“…BLAST analysis of the entire ITS region revealed that LE.170 strain had 99% similarity to Arthrographis curvata and to Arthrographis kalrae. The microscopic examination showed curved and cashew-nut-shaped arthroconidia, a feature characterizing A. curvata over A. kalrae [35]. The latter is known to have cylindrical with truncate arthroconidia [35].…”
Section: Discussionmentioning
confidence: 97%